Pemberdayaan Masyarakat Desa Trengguli melalui Sosialisasi Mitigasi Bencana Tanah Longsor dan Penghijauan (Reboisasi) - Immanuel Satrio Putro; Muhammad Husin Asidiq; Kusumaningdyah Nurul Handayani (Universitas Sebelas Maret, 2024)
Empowering the Trengguli Village Community Through Socialization of Landslide Disaster Mitigation and Reforestation. Efforts to empower the Trengguli Village Community, through the Landslide Disaster Mitigation Socialization work program, and also Reforestation as a concrete step in this socialization are programs designed and implemented with the aim of supporting Trengguli Village to become a landslide disaster response village. This program is included in the preventive program, where the program will help prevent landslides, and also help reduce the risks that occur due to landslides. This program not only involves KKN students from Sebelas Maret University, Surakarta, but also involves all elements of the village, starting from related village officials, and also support assistance from the Trengguli Village Community. It also involves a third party, namely the Solo River Basin Management Agency (BPDAS), as a party that helps provide plant seeds to be planted in areas prone to landslides. The implementation of these 2 programs is mutually sustainable and also related, by carrying out several stages of activities including: (1) Socialization activities for landslide disaster mitigation;(2) Determining and describing the location of areas prone to landslides; (3) Survey of landslide-prone locations as well as planting locations; (4) Replanting or reforestation in landslideprone areas in Trengguli Village. From the program that has been designed and implemented, the result is that the Trengguli Village Community has gained additional insight into landslide disaster mitigation from the socialization program, and the community can also convey their ideas or understanding about activities that can be carried out to help prevent landslides by filling out questionnaires. And the next thing is the planting of 100 plant seeds at several points in the landslide-prone areas of Trengguli Village, which it is hoped will be useful in preventing landslides, and is expected to inspire the enthusiasm of the Trengguli Village community to be able to continue these activities.